Trump Studies : an Intellectual Guide to Why Citizens Vote Against Their Interests. - Brabazon, Tara (Emerald Points Ser., 2018)
This book addresses the seismic political events of Donald Trump's presidency and the British vote to leave the EU. It explores why citizens vote against their own best interests, and demonstrates the role and value of universities in a time when evidence, expertise and facts often dissolve into opinion, emotion and fake news.